Хочу за науку замовити слово - Яцків, Я.С. (Вісник НАН України, 2019)
У статті співголови Ініціативної академічної групи «Наука та інновації» (ІАГ Н&І) Українського міжнародного комітету з питань науки і культури при НАН України наведено деякі міркування, напрацьовані в рамках ІАГ Н&І та Відділення фізики і астрономії НАН України, щодо питань, пов'язаних з назрілою сьогодні необхідністю трансформації науково-технологічної сфери України. Автор статті закликає представників академічної наукової спільноти долучитися до конструктивного обговорення цих проблем і визначити перші кроки на шляху до виходу з критичної ситуації, в якій опинилася зараз українська наука. На найвищому державному рівні необхідно якомога скоріше прийняти стратегію розвитку наукової сфери України та визначити основні її пріоритети. Подальше зволікання з цим питанням може призвести до незворотного зниження якості науково-технічного потенціалу країни. The article by the co-chairman of the Initiative Academic Group “Science and Innovation” (IAG S&I) of the Ukrainian International Committee on Science and Culture at NAS of Ukraine gives some considerations developed within the framework of IAG S&I and the Department of Physics and Astronomy of NAS of Ukraine on the pressing issues related to the need to transform the scientific and technological sphere of Ukraine. The author calls on the representatives of the academic scientific community to engage in a constructive discussion of these problems and to identify the first steps on the way out of the critical situation in which Ukrainian science is now. At the highest state level, it is necessary to adopt as soon as possible a strategy for the development of the scientific sphere of Ukraine and to determine its main priorities. Further delay on this issue can lead to an irreversible decline in the quality of the country's scientific and technical potential.